Healthcare Company Valuation (Case Study Of Hospital ABC) - Zayetri, Novia; Yudha Sudrajad, Oktofa (Journal of Economics and Business UBS, 2023)
The acquisition company of Ministry Stated-Owned Enterprise (SOE) are a very important issue in Indonesia. Similar to other SOE holdings, the hospital will be grouped and managed by PT Pertamedika IHC, and the acquisition will benefit Hospital ABC, IHC, and all company stakeholders. This study assessing Hospital ABC’s current business environment, determine forecast financial performance and determine Hospital ABC’s Equity valuation. This study analyses the environmental aspects of Hospital ABC, both external and internal, as well as the healthcare sector. Research methodology using both qualitative and qualitative and case study design. This study collects primary data through interview management and from secondary data, author makes projections based on financial statement reports. This study computes valuation using the discounted cash flow method. The results show that the value of Hospital ABC Equity about Rp.330.301 million, 679% higher than Equity in 2021. By calculating value of equity Hospital ABC, management could get additional data from preparation of acquisition process.